Birds - Dell, Pamela; Gai, Jackie (2017)
Take to the skies with songbirds and raptors, and waddle with some flightless birds, too! Organized by animal-science reference topics such as anatomy, migration, and life cycle, Birds introduces young readers and browsers to these feathered animals through full-color photos and concise, factual text.
What are birds? -- Part by part -- Feathered friends -- What birds do -- Raising a family -- What's for dinner? -- Nothing but nests -- On the move -- Water birds -- Tropical birds -- Flightless birds -- Birds of prey -- Bird-watching -- Fun facts.
Includes bibliographical references.
Ages 4-8.
K to grade 3.
Keywords: Birds -- Juvenile literature; Birds -- Encyclopedias, Juvenile